Existence and Uniqueness of Fixed Points of Generalized F-Contraction Mappings - A. P. Farajzadeh; M. Delfani; Y. H. Wang (Journal of Mathematics)
The newest generalization of the Banach contraction through the notions of the generalized F-contraction, simulation function, and admissible function is introduced. The existence and uniqueness of fixed points for a self-mapping on complete metric spaces by the new constructed contraction are investigated. The results of this article can be viewed as an improvement of the main results given in the references.